Effect of melt miscibility, polymorphism, and crystal morphology on tensile deformation of blends of isotactic polypropylene and propylene‐1‐hexene random copolymers. Issue 2 (23rd March 2020) - Janani, Hamed; Alamo, Rufina G.
Abstract: The ductile behavior of isotactic polypropylene (iPP) can be effectively increased by blending with small contents (<25%) of a random propylene 1‐hexene copolymer (PH). In this work, we have studied the uniaxial tensile deformation of binary blends of iPP with PH copolymers with 11 or 21 mol% 1‐hexene. Blends iPP/PH11 are melt‐miscible in the whole range of composition while iPP/PH21 blends are melt‐immiscible, but partially compatible. On cooling, the lamellar morphology of each type of blend differs accordingly, and impacts their mechanical deformation. Miscible iPP/PH11 blends develop inter‐mixed monoclinic lamellar stacks interconnected by tie molecules of iPP and PH admixed in the amorphous phase. During deformation, the monoclinic crystals transform to oriented mesophase at low strains due to effective stress transfer through the interconnected topology. These blends display the largest strain (~800%) and low recovery. Conversely, immiscible iPP/PH21 develop a coarser morphology of monoclinic and trigonal crystallites in the iPP‐rich and PH21‐rich domains, respectively. Less effective stress transfer associated with the coarse iPP/PH21 morphology leads to a delayed onset of orientation and a less effective monoclinic‐mesophase transformation. The PH21 trigonal crystals of the blend orient but do not undergo polymorphic transformation. At high elongations fibrillar strain‐induced trigonal crystals, provide a network of stable physical junction points that relax to the random orientation upon removal of the load, thus enhancing the elastic recovery of iPP/PH21 blends. Abstract : Enhanced elastic behavior of iPP is conferred by the addition of small contents of propylene 1‐Hexene copolymer. Highly interconnected lamellae from homogeneous melts of iPP/PH11 blends undergo more effective stress transfer, and monoclinic to mesophase transformation during deformation, than lamellae formed from phase separated melts of iPP/PH21 blends.